Tissue characterization using simultaneous estimation of backscatter coefficient and elastic shear modulus - Rouyer J. (2016)
Tissue characterization using quantitative ultrasound (QUS) parameters has received significant attention in recent years due to its potential to improve the detection and diagnosis of diseased states. However, the vast majority of studies in QUS tissue typing have used parameters derived from either longitudinal or shear waves in isolation, thereby discarding potentially useful complementary information these parameters may carry. In this study, the simultaneous estimation of backscatter coefficients (derived from longitudinal waves) and shear modulus (derived from shear waves) was implemented on data from a clinical scanner. Both parameters were estimated from five ex vivo porcine kidney samples and used to calculate the anisotropy ratio in the parameters when analyzing the middle and pole regions of the kidneys. For all samples, the estimated parameters were higher in the pole regions than in the middle region, with anisotropy ratios of 1.42±0.11 and 3.07±0.70 for the shear modulus and the backscatter coefficient, respectively. Therefore, these results demonstrate that QUS parameters derived from both longitudinal and shear waves can be estimated simultaneously and may be used in conjunction to track changes in tissue structure and composition. © 2016 IEEE.